Study on kratom usage effects at respiratory centre (brain stem) by functional MRI - Ramachandran, Renuka Devi (2023)
Background: Mitragyna speciosa (Korth.) or kratom is an indigenous medicinal plant native to Southeast Asia, a tropical tree (Mitragyna speciosa) that contains compounds that can have psychotropic effects. Kratom leaves can be freshly chewed or by decoction preparation for herbal use. Kratom has effects similar to both opioids and stimulants. Despite increasing usage across the globe, the potential side effects and respiratory depression due to prolonged use of kratom are still unclear. Functional magnetic resonance imaging (fMRI) is a non-invasive imaging method for measuring brain activity by detecting neurophysiological changes in cerebral blood flow to predict neuronal activation in the brain. Methods: 22 regular kratom adult kratom users and 20 non-kratom users who underwent fMRI for prior research were included in this cross-sectional study. A non-invasive neuroimaging technique measuring brain activity by detecting neurophysiological changes in the cerebral blood flow and thus predicting neuronal activation within the brain. The activation on fMRI images were transferred to SPM format and calculated using Mathlab SPM12. Results: Area of brain activation referred to kratom group was calculated P<0.05, at least, 4487 (Z value 6.78) and at P< 0.001 noted 10300(Z value 6.78). While, area of brain activation in non-kratom user group was calculated, noted at P< 0.05 only 5 (Z value 5.2) and at P<0.001, no activation was depicted at brainstem. This suggests respiratory depression in the brainstem noted within Kratom users. Conclusion: Overall study shows long-term consumption of kratom is associated with respiratory depression affecting the brainstem within Kratom users as we noted significant activation- higher cluster level seen within brainstem. On the other hand, minimal activation noted within the brainstem in non Kratom users. However, further studies are needed to establish more data on use of kratom and its effects on brain function using more invasive and diagnostic methods like analysing blood gas parameters for more accurate results.